Exposure to parental violence, child to parent violence and dating violence of Mexican youth - Cancino-Padilla, Daniela (2020)
Background: Violence is a serious problem that has generated worldwide concern because of the consequences it generates on those who suffer it. However, although it has been studied in its various forms, the study of violence against parents still has considerable research gaps. Therefore, this work had the objective of analyzing violence against parents, dating violence and observed between the parents to identify their frequency, as well as the possible correlations between them. Methods: The final sample was made up of 256 individuals between 18 and 30 years old. The Child to Parent Aggression Questionnaire-Revised and the Conflict Tactics Scale - Modified version were used. Results: The results indicated differences between the sexes regarding the incidence of both violence against parents and dating violence, as well as correlations between the variables studied and the bidirectionality in violence. Conclusion: It is important to investigate these phenomena more to understand them better, take the necessary measures and improve prevention and intervention programs.